(untitled) (Medical Forum Monthly, 2020)
Objective: to study the Comparative efficacy of intravenous levetiracetam vs phenobarbitone in neonatal seizures. Study Design: Observational Study Place and Duration of Study: This study was conducted at the Pediatric Department of Idris Teaching Hospital Sialkot from Jan2019 to Feb 2020. Materials and Methods: A total of 60 neonates of both gender with Neonatal seizures of less than 24 hours were included in the study. Patients who were already receiving anticonvulsants, seizures were due to correctable metabolic abnormalities (i.e. hypoglycemia, hypocalcemia, hypomagnesaemia, hyponatremia), neonates with associated pulmonary, hepatic, renal, or cardiac dysfunction were excluded. The antibiotic administration was based on departmental policy as 1st,2nd& 3rd line antibiotics and other drugs like intravenous fluids, blood products were according to the need for the patients. For anticonvulsant therapy we divided patients randomly into two groups Group A and Group B via lottery method. Group A was given inj phenobarbitone loading dose maximum 40mg/kg (initial loading dose 20mg/kg reloading with 10 mg/kg for further 2 times) and maintenance dose 5mg/kg. Group B was given injection Levetiracetam loading maximum40mg/kg(initially with 30mg/kg then reloading with 10mg/kg) and maintenance dose 20mg/kg/day. Both Drugs were given in infusion form in dilution in 15 ml normal saline over 15 minutes. All the procedures were done under supervision of a consultant pediatrician of three years post fellowship experience. If seizures reoccur with maximum loading dose then the patient was switched to other drug. Patient was continuous monitoring & observed for reoccurrence of seizure within 24 hours. Efficacy was noted. Results: Age range in this study was < 28 days with mean age of 15.200± 5.62 days in Group A while 14.900± 5.99 days in Group B. Mean duration of complain was 10.400±4.83 hours in Group A and 11.433±4.67 hours in Group B. Mean weight was 4.056±0.65 kg in Group A and 4.163±0.64 Kg in Group B. Male gender was dominant in both group (63.3% and 63.3%). In group A efficacy was seen in 9 (30%) patients as compare to 25 (83.3%) patients in group B, (P=0.000). Conclusion: It is concluded that levetiracetam is more efficacious than phenobarbital in control of clinical seizures in treatment of neonatal seizures.